The American Society of Peritoneal Surface Malignancies Multi‐Institution evaluation of 1, 051 advanced ovarian cancer patients undergoing cytoreductive surgery and HIPEC: An introduction of the peritoneal surface disease severity score. Issue 7 (December 2016) - Sleightholm, Richard; Foster, Jason M.; Smith, Lynette; Ceelen, Wim; Deraco, Marcello; Yildirim, Yusuf; Levine, Edward; Muñoz‐Casares, Cristobal; Glehen, Olivier; Patel, Asish; Esquivel, Jesus
Abstract : Background: Standard treatment for ovarian epithelial cancer (OEC) consists of cytoreductive surgery (CRS) and a platinum–taxane chemotherapy combination. There is increasing interest in evaluating hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with stage IIIC/IV disease. The peritoneal surface disease severity score (PSDSS) was introduced as a basis to improve patient selection for this therapy in OEC. Methods: The charts of 1, 051 patients with advanced OEC who underwent CRS/HIPEC were retrospectively evaluated using the following preoperatively obtained criteria: symptoms, peritoneal dissemination, and tumor histology. Overall survival was analyzed according to PSDSS as well as the timings and agents used during CRS/HIPEC. Results: Median survival for all 1, 051 patients was 73.4 months. PSDSS information was available for 553 patients. Survival correlated negatively with PSDSS ( P  < 0.001). Furthermore, combining PSDSS scores into I/II and III/IV described two distinct patient populations with vastly different outcomes, 100 versus 55 months, respectively ( P  < 0.001). Multivariate analysis failed to describe any differences between timings of HIPEC or chemotherapy agents used. Conclusion: PSDSS was capable of identifying a better surviving patient population in advanced‐stage OEC. While randomized trials to evaluate the benefit of HIPEC are needed, the PSDSS may be a useful tool for selecting and stratifying OEC patients in clinical trials. J. Surg. Oncol. 2016;114:779–784 . © 2016 2016 Wiley Periodicals, Inc.